Spatial patterns of adoption of just-in-time manufacturing - Adelheid Holl; Rafael Pardo; Ruth Rama (European Regional Science Association (ERSA), 2011)
We study the spatial pattern of Just-in-Time (JIT) adoption for a sample of medium-sized and large Spanish manufacturing firms. JIT differs from other advanced manufacturing technologies because it relates directly to the spatial coordination of a firms' internal production organisation with its external productive environment and depends on the quality of the transport system. Our results confirm the distinctive role of location for JIT adoption even after controlling for industry and plant-specific differences. We find that JIT adoption is greater in smaller cities but with higher transport accessibility indicating that urban congestion in larger urban areas likely reduces the benefits that firms may obtain from JIT implementation.
Keywords: 330